The Effect of the Read Aloud Method on Students’ Reading Interest at the Elementary Level - Indri Harmaili Lubis (JPI: Jurnal Pustaka Indonesia, 2026)
This study aimed to examine the effect of the Read Aloud method on the reading interest of third-grade students at SD Negeri 02 Sei Baru. Although reading interest is essential for establishing early literacy habits, empirical evidence on structured Read Aloud implementation in local elementary-school contexts remains limited. A quantitative quasi-experimental study employing a nonequivalent control-group design was conducted with 54 third-grade students: 27 students in the experimental group and 27 in the control group. Data were collected through a reading-interest questionnaire covering enjoyment of reading, reading frequency, curiosity toward reading materials, and awareness of reading importance. Descriptive statistics, paired-sample t tests, and an independent-sample t test were used to analyse the data. The experimental group’s mean score increased from 58.44 at pretest to 82.15 at posttest, whereas the control group increased from 59.11 to 68.85. Posttest results showed a statistically significant difference between the groups (p = .002). These findings indicate that the Read Aloud method was associated with higher reading interest among participating students. The result suggests that expressive storytelling, interactive questioning, teacher scaffolding, and reflective discussion can create more enjoyable and meaningful literacy experiences for young learners. However, the findings are limited to one school and a relatively small sample; broader studies across varied educational settings are needed. Integrating Read Aloud activities into regular literacy instruction may therefore support the development of sustained reading interest in elementary education.